Digital measurement of ocular microtremor in Parkinson's disease: Protocol for a pilot study to assess reliability and clinical validation. - Lisa Graham; Rodrigo Vitorio; Richard Walker; Alan Godfrey; Rosie Morris; Samuel Stuart (PLoS ONE)
Ocular microtremor (OMT) is a fixational eye movement that cannot be seen with the naked eye but is always present, even when the eye appears motionless/still. The link between OMT and brain function provides a strong rationale for investigation as there lies potential for its use as a biomarker in populations with neurological impairments. OMT frequency is typically 70-80Hz in healthy adults and research suggests that this will be reduced in those with neurological disease such as Parkinson's Disease (PD). This study aims to examine OMT in people with PD compared to healthy older adults. This is an exploratory, observational study that will use a novel handheld device-The iTremor ONE, which has been developed to rapidly, non-invasively assess and evaluate OMT frequency. This device uses incident laser technology directed at the sclera. People with PD who meet the inclusion criteria will participate in a home-based assessment involving cognitive, motor (using the UPDRS-III) and OMT measures. With OMT as the primary outcome, assessment with the iTremor is quick, taking just three seconds to obtain a reading. People with PD will be invited into the laboratory to perform extensive cognitive assessments along with an assessment of balance, gait, and turning using wearable sensors. People with PD will be assessed both off, and on, their anti-parkinsonian medication following a 12 hour washout period. We will recruit 30 People with PD, 30 people with suspected PD and 30 age-matched healthy control participants for assessment of OMT. 20 People with PD will complete a test-retest reliability assessment at the same approximate time, exactly one week after their initial visit under the same conditions to explore consistency. This will be the first study of its kind to non-invasively investigate OMT frequency as a marker/monitor for PD with advanced technology that could be used within the clinic, laboratory, or home. Identifying OMT as a PD biomarker could better support clinical assessment, enabling improved provision of care to patients with advanced disease monitoring. Clinical trial registration: This trial is registered at clinicaltrials.gov (NCT06051877; September 2023).